Case Report: Expanding Clinical, Immunological and Genetic Findings in Sideroblastic Anemia With Immunodeficiency, Fevers and Development Delay (SIFD) Syndrome - Mendonca, Leonardo Oliveira; Prado, Alex Isidoro; Costa, Izelda Maria Carvalho; Bandeira, Marcia; Dyer, Rafael; Barros, Samar Freschi; Khöler, Karen Francine; Fonseca, Luiz Augusto Marcondes; Kalil, Jorge; Castro, Fabio Morato; Toledo-Barros, Myrthes Anna Maragna (Frontiers in Immunology, 2021)
Since the first description of the syndrome of sideroblastic anemia with immunodeficiency, fevers and development delay (SIFD), clinical pictures lacking both neurological and hematological mani-festations has been reported. Moreover, prominent skin involvement, such as with relapsing erythema-nodosum is not a common finding. Up to this moment, no genotype and phenotype correlation could be done, but mild phenotypes seems to be located in the N or C part. B cell deficiency is a hallmark of SIFD syndrome and multiple others immunological defects have been reported, but not high levels of double negative T cells. Here we report a Brazilian patient with a novel phenotype of SFID syndrome, carrying multiple immune defects and harboring a novel mutation on TRNT1 gene.